Estimasi Permintaan Air Minum Dalam Kemasan Ayia Cup 240 Ml Pada PT. Gunung Naga Mas - Riko Ervil; Mela Rosalina (Universitas Negeri Padang, 2019)
Consumer demand is very important in industrial activities at this time, because the new production process will run if there is demand from consumers. The problem that exists at PT Gunung Naga Mas is that the company produces goods without considering market demand, resulting in increased storage costs and also items that are long stored will be damaged. For this reason, it is necessary to forecast demand with linear trend methods, quadratic trends and exponential trends. From the purpose of the study it can be concluded that the most effective method for predicting demand for drinking water in 240 ml cup packaging at PT. Gunung Naga Mas is a linear trend method with MSE value of 544,291,863 and forecast demand for drinking water products in 240 ml cup packaging at PT Gunung Naga Mas in 2018 which is a total of 1,918,768 boxes. So the Company needs to adjust production capacity in 2018.